Comportamento informacional de surdos em bibliotecas universitárias - França, Maísa Coelho (Universidade Federal de São Carlos, 2024)
The 2022 Higher Education Census conducted by the Anísio Teixeira National Institute for Educational Studies and Research (INEP) revealed that 2,592 individuals with hearing impairments were enrolled in Higher Education institutions across Brazil. The presence of deaf individuals in Higher Education necessitates the adaptation of university libraries to meet this demand. This entails an awareness of deaf culture to serve the deaf community effectively. This research aimed to investigate the information behaviour of deaf users who use (or have used, in the case of those who have already graduated) university libraries during their academic training. To investigate information behaviour, this research drew upon the theories of Wilson (information behaviour models), Dervin (sense-making), and Chatman (small world). The data were collected via an online questionnaire developed in Brazilian Sign Language, comprising three open-ended questions, 14 multiple-choice items, nine statements on a Likert scale of agreement, and one field for suggestions. The questionnaire was e-mailed to 199 Brazilian Higher Education institutions, deaf associations, and individuals from the deaf community, including interpreters. The snowball sampling technique was employed to gain access to the deaf community. A total of 95 responses were obtained, and the results demonstrate that the survey participants hold undergraduate, technologist, specialisation, Master's, and Doctoral degrees. Among the respondents, 18% do not use their institution's library facilities. However, among those who do, they report that library environments are conducive to the needs of deaf individuals, to the extent that they are recommended to other deaf people, irrespective of accessibility and collection issues. Of all the participants, 62% typically visit the library independently. Nevertheless, those who do not feel at ease reading and writing in Portuguese typically attend the library accompanied by other deaf individuals. A majority of participants exhibited a notable inclination towards human sources when searching for information, and 65% demonstrated the ability to identify reliable information, while 68% asserted their capacity to assess the usefulness of the information they retrieve for their information needs. Furthermore, regarding the theories employed, it was possible to discern the 'intervening variables' (demographic, environmental, and source characteristics) and the 'risk/reward theory' of Wilson's information behaviour model; the impact of context and variables such as security, values, and attitudes in facilitating the process of sense-making, as proposed by Dervin; and certain characteristics of the deaf respondent community that align with the concept of a small world, as postulated by Chatman. It is incumbent upon the university library to provide access to quality information from reliable sources. Librarians must work to eradicate possible contexts of information poverty. The task of understanding the deaf community is a complex one, which extends far beyond Brazilian legislation that guarantees their rights, including linguistic rights. Constructing a genuinely inclusive university library environment for these individuals – and not only for them – the library and its professionals must demonstrate a keen awareness of their community and the evolving trends within society. It is essential to adopt a welcoming and inclusive approach towards deaf individuals to facilitate their access to information resources and support their academic training.
Information behaviour of Deaf people in university libraries
Keywords: Surdos; Bibliotecas universitárias; Comportamento informacional; Deaf; Information behaviour; University libraries; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO